Evaluating the long-run impact of an innovative anti-poverty programme: evidence using household panel data - Asadullah, M.N.; Ara, J. (Taylor & Francis, 2016)
Using a four-round panel data set from the first phase of the Challenging the Frontiers of Poverty Reduction – Targeting the Ultra Poor (CFPR – TUP) programme of BRAC, we investigate whether a one-off transfer of livestock assets improves well-being of the very poor women in Bangladesh. Programme impact is assessed on a wide range of monetary and nonmonetary measures of well-being using difference-in-difference (DD) as well as matching methods. We find significant positive long-term impact on food security, household savings, assets and participation in microfinance. Participant women are less likely to be in distress occupation and more into self-employment. However, the long-term effect is much smaller for most outcomes when compared to short- and medium-run impacts. We conclude by discussing the significance of the institutional and regional context for the observed time path of estimated programme effect.